Assessing the Knowledge of Universal Student about Mental Illness in Al-Najaf City - M. Razaq, Hani; H. Mohammed, Saja (International Journal of Psychosocial Rehabilitation, 2020)
Mental health and mental illness are important topics for every individual, family, and everyone in society. Increasing this knowledge about mental illness is important and necessary for all members in society. A cross-sectional study was included with 80 universal students. The study aimed to assess the students knowledge about mental illness, as well as to find any significant relationship among the level of knowledge and their demographic characteristics. A purposive sample was used to select students to participate in the study. A tool of study contains two main parts. The first part included questions related to the demographic characteristics of students. The second part related to assessing the knowledge of mental illness in students. The results revealed 57.5% of students had a moderate level of knowledge about mental illness, while 18.75% had a good level of knowledge. More than the study result showed nonsignificant relationships between selected demographic characteristics of students and their knowledge. The study is recommended to establish special multidisciplinary plan among Ministries of Health and Education to increasing the knowledge about mental illness and Further study should be conducted on a large representative sample to know the public knowledge in society about mental illness, especially focusing on young people.